Barnés Vázquez, A. Magda Kučerková, M. (eds.), The Figurativeness of the Language of Mystical Experience. Particularities and Interpretations, Brno, Masaryk University Press, 2021, 279 pp., ISBN 978-80-210-9997-5 - Lasticova, Adriana ('Ilu. Revista de Ciencias de las Religiones, 2022)
C'est le compte-rendu de:Barnés Vázquez, Antonio & Magda Kučerková (ed.), The Figurativeness of the Language of Mystical Experience. Particularities and Interpretations. Brno, Masaryk University Press, 2021, 279 pp., ISBN 978-80-210-9997-5.